Prevalence and outcome of extra-cardiac findings in patients referred for cardiac computed tomography angiography. (14th October 2021) - Nashat, H; Adjei, F; Enver, K; Halmai, L; Kardos, A
Abstract: Background: Cardiac computed tomography angiography (CCTA) includes several extra-cardiac structures. A variety of abnormalities may be clinically important and, in some cases, explain the patient's symptoms. The incidence of extra cardiac findings (ECFs) on CCTA examination ranges between 7% and 56%, with the true prevalence likely affected by patient selection. Methods: Cardiac CT scans with suspected coronary disease were prospectively and independently reviewed by a radiologist for the presence of ECFs. Data was collected from a prospectively collated database of all patients who underwent a CCTA scans between June 2011 and October 2015. Patients were followed up for one year after incidental findings were made. Results: A total of 635 patients had a CCTA scan during the study period. Of these 325 (51.2%) were male, mean age was 66 [22–88] years, with a mean BMI of 27 [17–56]. Extra-cardiac findings were reported in 126 (19.8%) of these 62 (49%) were classified as clinically important and had further imaging and follow-up. The most common abnormalities were pulmonary nodules 61 (46.8%), Hiatus hernia 15 (12%), lymphadenopathy 12 (10%) and liver cysts 10 (8%), Figure 1a. Malignant tumours were identified in 2 (1.6%) patients and one (0.8%) had both aortic root dilatation and type B aortic dissection. Conclusion: Non-cardiac abnormalities in patients undergoing CCTA provides useful information e.g. early diagnosis of lung malignancies and other life threatening conditions in up to 40% of patients. Funding Acknowledgement: Type of funding sources: None.